Keterampilan literasi informasi sebagai upaya pencegahan hoaks mengenai informasi kesehatan di media sosial - Tine Silvana Rachmawati; Merryam Agustine (Jurnal Kajian Informasi dan Perpustakaan, 2021)
People must know how identify and search for credible health information. This study aimed to determine how information literacy activities prevented the spread of health information hoaxes on social media. This study used a qualitative approach and case study research methods. The collect research data through observation, interviews with 15 interviewees, and literature study techniques. The study results found that people obtained health information literacy by utilizing social media that is used daily. First, people recognized when they needed information, meaning they already understood when to search for information and knew what information to seek. Second, people can find information was performed in various ways, such as choosing a mass media portal that was easy to use, searching for specific information by including keywords or hashtags. Third, people evaluate the information found by knowing who made the information. Who disseminates the information? Are social media accounts trustworthy? Does the skill match the required information? Fourth, people use the obtained information effectively. People only chose the information that was suitable for what they felt and needed. Conclusion this research is people that who use social media must have information literacy expertise in finding health information so that avoid hoax information widely circulating today.